Pemberitaan Pidato Pribumi Anies Baswedan Pada Media Indonesia.Com dan Okezone.Com - Didik Hariyanto; Dyah Ayu Kharina (Universitas Muhammadiyah Sidoarjo, 2018)
Okezone.com in the case of speeches that professed indigenous words by DKI Jakarta Governor Anies Baswedan. This research uses descriptive qualitative method with framing analysis from Robert N. Entman which consists of define problems, diagnose couses, make moral judgement and treatment recomendation. The theory used to see the truth in the context of framing analysis study is the second stage of agenda setting from Mc Combs. The results of this study are Media Indonesia.com and Okezone.com in presenting news about indigenous speeches by Anies Baswedan are not neutral. In accordance with the second stage of agenda setting Mc Combs that highlighted is attribute. The attribute referred here is indigenous word which refers to the Dutch designation to demean Indonesian citizens, indigenous words discriminate race and ethnicity, indigenous words can divide Indonesian citizens, and indigenous words not worthy of saying.